2016
DOI: 10.1007/s40641-016-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability in Tidal Range: Evidence, Causes, and Effects

Abstract: Tidal range is one factor in determining the vertical location of local mean sea level, and it is also a contributor to total water levels and coastal flooding. It is therefore important to understand both the spatial distribution of tidal range and the temporal variation in tidal range, over a wide range of scales. Knowledge of historic tidal range is obtained both through observations and through modeling. This paper reviews numerous observational and modeling studies of historic tidal range variations on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 126 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…As Hill () points out, paleo–time scales have occupied much of the attention of past modeling work on large‐scale changes in tides (section ), while navigational impacts over the last few centuries have been a primary focus of local modeling and data analysis (section ). However, recent studies have been increasingly geared toward prediction of future changes in tides over the 21st century and beyond, motivated by concerns regarding climate change, particularly MSL rise (e.g., Holleman & Stacey, ) and changes in coastal flooding (see section ).…”
Section: Future Changes In Tides and Implicationsmentioning
confidence: 99%
“…As Hill () points out, paleo–time scales have occupied much of the attention of past modeling work on large‐scale changes in tides (section ), while navigational impacts over the last few centuries have been a primary focus of local modeling and data analysis (section ). However, recent studies have been increasingly geared toward prediction of future changes in tides over the 21st century and beyond, motivated by concerns regarding climate change, particularly MSL rise (e.g., Holleman & Stacey, ) and changes in coastal flooding (see section ).…”
Section: Future Changes In Tides and Implicationsmentioning
confidence: 99%
“…Several factors have been discussed as responsible for changes in the tidal characteristics observed in other regions. At global scale, these factors are the rise of MSL and changes in ocean stratification, while at local scale morphological changes (i.e., dredging, land reclamation) can also modify tide characteristics ( see e.g., Woodworth, 2010;Müller, 2011;Devlin et al, 2014;Hill, 2016).…”
Section: Tidal Analysismentioning
confidence: 99%
“…While trying to assess changes in extreme WLs tides have been assumed to remain constant, although some recent studies have reported significant positive and negative trends in tidal levels and tidal constituents in most regions of the world (Woodworth and Blackman, 2004;Jay, 2009;Ray, 2009;Haigh et al, 2010;Woodworth, 2010;Müller, 2011;Feng et al, 2015;Mawdsley et al, 2015;Hill, 2016). However, secular tidal changes in Buenos Aires and Mar del Plata have not yet been analyzed and have therefore not been considered in previous studies on the trends and variability of storm surges Fiore et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…could match observed trends but only by invoking an unphysically large subsidence rate, centered at the shelf break, to their adopted bathymetry.) It seems likely that additional factors (e.g., Hill, ), perhaps related to secular changes in ocean stratification (Müller, ), may be playing a role.…”
Section: Introductionmentioning
confidence: 99%